Case Report: Clinical and MRI features of hemorrhagic transformation of an ischemic cerebrovascular accident in a dog - Bellomo, Alessandro; Mattei, Chiara; Capasso, Michele; Bernardini, Marco; Balducci, Federica (Frontiers in Veterinary Science, 2025)
IntroductionHemorrhagic transformation (HT) is a known complication of human ischemic cerebrovascular accidents (CVAs), resulting from blood–brain barrier disruption and reperfusion. This report describes the magnetic resonance imaging (MRI) features of a clinically suspected HT after ischemic CVA in a dog.Case presentationAn eight-year-old spayed female mixed-breed dog presented with peracute onset of left-sided forebrain clinical signs. A brain MRI, performed within 12 h from the onset of clinical signs, revealed a large area of restricted diffusion, almost undetectable in the other MRI sequences, encompassing the vascular territory of the left middle cerebral artery, suggesting a peracute ischemic CVA. In the subsequent 24 h, the dog showed severe clinical deterioration, suggesting brainstem involvement. A 40-h follow-up MRI revealed an extensive area of signal void on Susceptibility-Weighted Imaging in the same vascular territory, with severe mass effect, indicating HT of the previous ischemic CVA.DiscussionRapid and severe clinical deterioration in a dog previously diagnosed with ischemic CVA should raise suspicion of HT and warrant further MRI evaluation.